Southern Africa : old treacheries and new deceits - Chan, Stephen, 1949- (Yale University Press, 2011)
In this timely and essential book, Stephen Chan explores the political landscape of southern Africa, examining how it's poised to change over the next years and what the repercussions are likely to be across the continent. He focuses on three countries in particular: South Africa, Zimbabwe, and Zambia, all of which have remained interconnected since the end of colonial rule and the overthrow of apartheid. One of the key themes in the book is the relationship between South Africa and Zimbabwe, and Chan sheds new light on the shared intellectual capacities and interests of the two countries' respective presidents, Jacob Zuma and Robert Mugabe. Along the way, the personalities and abilities of key players, such as Morgan Tsvangirai, the prime minister of Zimbabwe, and former South African president Thabo Mbeki, emerge in honest and sometimes surprising detail. In Southern Africa, Chan draws on three decades of experience to provide the definitive inside guide to this complex region and offer insight on how the near future is likely to be a litmus test not just for this trio of countries but for all of Africa.